Cost-effectiveness analysis of coronary arteries bypass grafting (CABG) and percutaneous coronary intervention (PCI) through drug stent in iran: a comparative study - NourolHoda Fakhrzad; Mohsen Barouni; Reza Goudarzi; Javad Kojuri; Yunes Jahani; Mohammad Tasavon Gholamhoseini (Cost Effectiveness and Resource Allocation, 2023)
Abstract Background Cost-effectiveness analysis plays a key role in evaluating health systems and services. Coronary artery disease is one of the primary health concerns worldwide. This study sought to compare the cost-effectiveness of Coronary Arteries Bypass Grafting (CABG) and Percutaneous Coronary Intervention (PCI) through drug stent using Quality-Adjusted Life Years (QALY) index. Methods This is a cohort study involving all patients undergoing CABG and PCI through drug stent in south of Iran. A total of 410 patients were randomly selected to be included in the study. Data were gathered using SF-36, SAQ and a form for cost data from the patients' perspective. The data were analyzed descriptively and inferentially. Considering the analysis of cost-effectiveness, Markov Model was initially developed using TreeAge Pro 2020. Both deterministic and probabilistic sensitivity analyses were performed. Results Compared with the group treated with PCI, the total cost of interventions was higher in the CABG group ($102,103.8 vs $71,401.22) and the cost of lost productivity ($20,228.68 vs $7632.11), while the cost of hospitalization was lower in CABG ($67,567.1 vs $49,660.97). The cost of hotel stay and travel ($6967.82 vs $2520.12) and the cost of medication ($7340.18 vs $11,588.01) was lower in CABG. From the patients' perspective and SAQ instrument, CABG was cost-saving, with a reduction of $16,581 for every increase in effectiveness. Based on patients’ perspective and SF-36 instrument, CABG was cost-saving, with a reduction of $34,543 for every increase in effectiveness. Conclusion In the same indications, CABG intervention leads to more resource savings.